Cranial and Peripheral Interictal Vascular Changes in Migraine Patients - de Hoon, JN; Willigers, JM; Troost, J; Struijker-Boudier, HA; Van Bortel, LM (Cephalalgia, 2003)
As migraine is associated with an increased risk for ischaemic stroke and peripheral vasospastic disorders, it was hypothesized that interictal vascular changes may be present in migraine patients. Using ultrasound and applanation tonometry, the cardiovascular properties of migraine patients were compared with those of matched control subjects. Vascular parameters of the carotid arteries, cardiac output and systemic vascular resistance did not differ between both groups. Right temporal artery diameter was larger in migraine patients (mean difference 101 μm; 95% confidence interval (CI) 9/194 μm; P = 0.033). At the brachial artery, migraine patients displayed a smaller distension (difference -24 μm; 95% CI -45/-4 μm; P = 0.021) and a decreased compliance (difference -0.025 mm2/kPa; 95% CI -0.047/-0.003 mm2/kPa; P = 0.024). Thus, migraine patients display an increased peripheral arterial stiffness. The presence of these interictal vascular changes suggests that migraine might be part of a more generalized vascular disorder.